MARHATA-HATA DALAM UPACARA MARHORJA DI NAGARI KOTA NOPAN KECAMATAN RAO UTARA KABUPATEN PASAMAN - Nurhidayati, Nurhidayati; Nasution, Bakhtaruddin; Nasution, Muhammad Ismail (Universitas Negeri Padang, 2012)
The results showed that the structure marhata-hata comprising the structure of the story and the narrator are circumstances and situations on the show or things that affect the outside structure of the show include the atmosphere, audience, players, history, atmosphere of the show, and tools. Position as follows: first, the values ​​contained in marhata-hata, for example: the value of harmony, spiritual values ​​and social values​​. Second, as a complement to the marhorja (marriage). Marhata-hata function in society, among others: (1) the function of entertainment, by listening marhata-hata all the sadness that is felt listeners will be lost, (2) the function of education, someone who has been impregnating or understand marhata-hata will have language which means both polite and not condescending to others, (3) social function, values​​: tolerance, responsibility, and suave or polite, (4) the function of language, through marhata-hata is preserved regional languages ​​and culture of the region, (5) custom function, people who do not understand or comprehend marhata-hata regarded as people who do not know the customs, (6) the atitude function, marhata-hata could lead a person to behave well, and (7) the function of religion.